Lead Firms in the Cocoa–Chocolate Global Production Network: An Assessment of the Deductive Capabilities of GPN 2.0. (8th August 2018) - Neilson, Jeff; Pritchard, Bill; Fold, Niels; Dwiartama, Angga
Abstract: Recent models of Global Production Network Theory (known as GPN 2.0) have attempted to theoretically explain the underlying determinants, or causal drivers, of particular industry network configurations, which in turn shape the territorial outcomes for regional development. To date, the ability of this ambitious conceptual model to thereby explain economic geography has remained largely untested beyond the select industry networks examined by its proponents, most notably the electronics, retail, and automotive sectors of East Asia. In this article, we stress test the causative model for the case of lead firms in the global cocoa–chocolate sector, and assess its ability to subsequently explain industry configurations and territorial outcomes in a particular country: Indonesia. Our application suggests that GPN 2.0 has considerable utility for directing empirical research, but challenges beset its fuller theoretical promise. We identify a problematic relationship between the deductive causality implied by GPN 2.0 and the inherent relationality of GPN 1.0 that remains, in our view, unresolved. As a result, we remain skeptical of the broader theoretical claims that GPN 2.0 possesses explanatory powers capable of deducing industry network configurations from a discrete set of supposedly independent variables.